On systematic status of Spindasis syama Horsfield, [1829] in Taiwan and the Philippines (Lepidoptera: Lycaenidae: Aphnaeini) - Hsu, Yu-Feng; Liang, Jia-Yuan (Zootaxa, 2020)
Based upon both morphological and gene barcode evidence, the population of Spindasis syama in Taiwan is described as Spindasis syama lamuae, ssp. nov., and the taxon negrita Felder, 1862 is revised as a species endemic to the Philippines (stat. rev.).